Semantic Analysis of Synecdoche Pars Pro Toto and Totem Pro Parte in Qs. al-Baqarah - Damhuri, Damhuri; Ratni Bt. Hj. Bahri; Akib, Nasri (LP2M IAIN Sultan Amai Gorontalo, 2024)
This article explores and analyzes the meaning of synecdoche, specifically, the forms pars pro toto and totem pro parte, as found in Surah Al-Baqarah. The study employs a qualitative approach, with the Quran as the primary data source. Data were collected using note-taking and free-listening techniques and were analyzed through the adoption of Lakoff's cognitive analysis technique. The findings reveal the presence of both pars pro toto and totem pro parte synecdoches in Surah Al-Baqarah. Examples of pars pro toto include references to parts of prayer (such as standing, bowing, dhikr, and prostration) representing the entire prayer, parts of the body (neck, hands, and face) representing the whole body, and parts of a place (Masjid al-Haram and Kaaba) representing the entire place. Conversely, examples of totem pro parte include references to the whole of a limb (finger) representing a part of it (fingertip) and the whole of a period (moon) representing a part of it (hilal). These findings contribute to a deeper understanding of the use of synecdoche in Quranic language, highlighting its role in enriching the textual and interpretive dimensions of the scripture.